Evaluation of 24 hours urinary fluoride excretion of children aged 4-5 years participating in the milk fluoridation programme, Bangkok - เล็กเฟื่องฟู, พวงทอง; นิยมศิลป์, กรกมล (Thai Dental Public Health Journal, 2008)
The aim of this study was to compare the 24-h urinary fluoride excretion rates of 4-5 year old school children participating in the milk fluoridation programme in Bangkok (n=30) with a control group (children of the same age, not exposed to F-milk) in Samut Prakarn province (n=29). The concentration of fluoride in the water in both districts is approximately 0.1 - 0.2 ppm. and investigations showed that the use of fluoridated toothpaste by both groups was similar. Each child's urine was collected over 24- h. Supervised collection of the urine samples was made during the school day by the research team and separated into two periods( those taken before the consumption of fluoridated milk and those taken after). In the third period, the intervening hours at home, samples were collected by the parents of the participating children. The urinary volume and urinary flow for each of the three periods were determined. Urinary fluoride concentration and urinary fluoride excretion rate per hour were also calculated. The average 24-h urinary fluoride excretion was higher in the group consuming fluoridated milk than in the control group: 346.91 ( 89.93) and 207.69 ( 106.08) _g respectively. The average 24-h urinary fluoride concentrations were 0.63 (_ 0.23) and 0.35 ( 0.12) ppm. in the group consuming fluoridated milk and the control group respectively. With reference to the provisional standards for urinary fluoride excretion and concentrations (WHO) both the average total 24-h urinary fluoride excretion and the urinary fluoride concentration of the children consuming fluoridated milk were shown to be within acceptable limits. In conclusion the study demonstrates that the children participating in the milk fluoridation programme in Bangkok do not appear to have an increased risk of dental fluorosis.